Vacancy pair-induced charge rebalancing with surface and interfacial dual polarization for CO₂ photoreduction - Di, Jun (2023)
Poor charge kinetics greatly reduce the efficiency of photocatalytic CO2reduction. Herein, a synchronous surface and interfacial dual polarization strategy was developed to promote charge separation. Bi-O vacancy pairs in Bi24O31Br10atomic layers can trigger strong coupling between black phosphorus (BP) and Bi24O31Br10, forming a restructured closely contacted BP-Bi24O31Br10configuration with a charge-redistributed interface via electronegativity-induced charge rebalancing. The Bi-O vacancy pairs on the surface of Bi24O31Br10and restructured BP/Bi24O31Br10interface enable synchronous surface and interfacial dual polarization, creating an electronic bridge from the interior of Bi24O31Br10to the BP surface, as proven by ultrafast transient absorption spectroscopy. This configuration favors a low CO2activation energy barrier, effectively stabilizes COOH∗ intermediates, and decreases the rate-determining step energy barrier. Benefiting from these features, the stable CO generation rate of optimized BP-Bi24O31Br10reaches up to 39.8 μmol g-1h-1via CO2photoreduction in water, which is 2.4 and 46.8 times higher than those of defective Bi24O31Br10atomic layers and defect-poor Bi24O31Br10, respectively. This study provides insights into the synchronous design of surface defects and restructured interfaces for dual polarization.